Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik pada Muatan IPA Menggunakan Model GREAT - Husnul Hatimah; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The research carried out in class IV at SDN Alalak Selatan 2 was motivated by the low activity and learning outcomes of students. The use of one-way teaching methods, monotonous and uninteresting learning processes, less innovative and varied learning models or methods, and students only learning passively and rarely having group discussion activities are the causes of the problems faced. Therefore, improvements were made using the GREAT model. The aim of this research is to describe teacher activities, analyze student activities, and student learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (PTK) which was carried out in 4 meetings. This research uses qualitative and quantitative data. The research results show that teacher activity at meeting 1 to meeting 4 increased from a score of 21 to a score of 32, student activity from meeting 1 to meeting 4 increased from 45% to 100%, and cognitive learning outcomes at meeting 1 to meeting 4 increased from 27% to 100%. Based on these findings, it can be concluded that using the GREAT model can improve learning activities and student learning outcomes. It is suggested that this research can be an alternative or reference for determining innovative and varied learning models in improving learning activities and student learning outcomes.